Genetic variation analysis of a primary immunodeficiency patient via whole-exome sequencing approach / Bader Abdul Kader El Farran - Bader Abdul Kader , El Farran (2021)
Primary Immunodeficiency (PID) refers to a collection of diseases whereby the production of antibodies is negatively affected, or the cellular defenses of the immune system do not operate appropriately. A Malaysian patient (P1) was initially suspected with a PID type known as Hyper IgM syndrome. However, the immunological workup was not compatible with Hyper IgM syndrome. Hence, a Whole-exome sequencing (WES) analysis was conducted to look for mutations in PID-related genes. P1’s raw data were mapped to four different versions of the human reference genome to compare the results and determine which one is the best for this analysis. Once the variants were called from P1’s data they were annotated to search for mutations. As a result, a novel mutation was detected in the Nuclear factor-kappa-B-inhibitor alpha (NFKBIA) gene, which is responsible for regulating the Nuclear factor-kappa-B (NFKB) gene. It is a single nucleotide polymorphism (SNP) (NFKBIA:NM_020529:exon1:c.A94T:p.S32C) at codon 94 (c.A94T) of P1’s NFKBIA gene which resulted in the mutation of the serine residue (Ser32) to a cysteine residue (Cys32). This SNP lies in the destruction motif of the NFKBIA protein, which may have led to the impairment of NFKB activation in P1, which could explain the symptoms of the patient. Since this is a novel mutation, it warrants future investigation to find out what such mutation exactly does to the NFKBIA protein structure and how it affects its interaction with NFKB.